Comorbidity of unipolar depression in patients of psoriasis attending a tertiary care hospital - Pranjal Dey; Rakesh Mohanty; Jyoti Nath; Mukherjee Aniruddha (Archives of Mental Health, 2019)
Context: Psoriasis is one of the most common dermatological illnesses with an often-devastating course. Patients of psoriasis have impairment of physical, psychological, vocational, social functioning which led to psychiatric morbidities such as anxiety disorders and depressive disorder. Aims: The objective is to evaluate the presence and severity of depression in patients of psoriasis and to correlate the severity of psoriasis with severity of depression. Settings and Design: Hospital-based cross-sectional study. Subjects and Methods: Fifty patients of psoriasis were enrolled for the study after their informed consent with purposive sampling method from the Department of Dermatology, in a tertiary care hospital in northeastern part of India. The severity of psoriasis was assessed using Psoriasis Area and Severity Index scale. Same patients were evaluated using international classification of diseases 10 research criteria and Hamilton rating scale of depression to diagnose and grade the degree of depression. Statistical Analysis Used: Linear regression method was used to compare the severity of depression with the severity of psoriasis. Data were analyzed in SPSS version 20.0. Results: Incidence of depression was found to be 44% in psoriasis patients. Among them, 50% had mild depression, and 36.1% had severe to very severe depression. The severity of depression was directly proportionate to the severity of psoriasis. Conclusions: These findings indicate the need of early recognition of depression among these patients and their early intervention, which will improve the primary disease process.